Dasar Pertimbangan Yuridis Kedudukan Hukum (Legal Standing) Kesatuan Masyarakat Hukum Adat dalam Proses Pengujian Undang-Undang di Mahkamah Konstitusi - Nur Rahman, Irfan; Triningsih, Anna; Harumdani W, Alia; Kurniawan, Nallom (Mahkamah Konstitusi Republik Indonesia, 2011)
In the context of history and politics, in fact, indigenous people have been there ahead of the country of Indonesia. Protection of customary law community unit to defend their constitutional rights if there are laws that harm their constitutional rights. But there are certain requirements that must be met in order for customary law community unit having legal domicile (legal standing) to file a petition for legislation in the Constitutional Court because not all indigenous people have legal standing in testing the law. This of course has the legal implications on the recognition, respect and protection of customary law community unit, namely the unity of indigenous people that still exist are not automatically recognized as customary law community unit unless it has to meet certain constitutional requirements set out in the 1945 post-change.The purpose of the conduct of this research is to discover, deepen and develop ideas related to concepts, theories, principles of legal and normative provisions concerning the legal status of customary law community unit in the proceedings in the Constitutional Court.Requirement for customary law community unit in order to have legal status (legal standing) as the applicant in the testing of the Act is quite heavy, but must prove himself as a customary law community unit as referred to in Article 51 paragraph (1) letter b Law the Constitutional Court, must also meet 5 (five) loss of constitutional requirements as specified in jurisprudence of the Constitutional Court. The legal position because of the weight requirement (legal standing) for customary law community unit, until now there is no applicant who claims to customary law community unit, has a legal domicile (legal standing) in testing the law. Typology and benchmarks about who is categorized as a customary law community unit is still not clear, so that through decision No. 31/PUU-V/2007, the Court gave typology and size of the unity of indigenous people by interpreting Article 18B paragraph (2) of the 1945 Constitution